2008
DOI: 10.1001/archpedi.162.11.1048
|View full text |Cite
|
Sign up to set email alerts
|

Additional Visit Burden for Universal Influenza Vaccination of US School-Aged Children and Adolescents

Abstract: Most children and adolescents would need additional visits for universal influenza vaccination, even if all existing visits were used as vaccination opportunities. Efficient methods for vaccinating large numbers of children and adolescents are needed if primary care practices are to provide influenza vaccine for all children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Among children aged 9 to 18 years, at least 75% would need 1 extra visit. 39 To be maximally effective and avoid missed opportunities to prevent early season infections, vaccination should occur as early as possible, beginning as early as September. Strategies to reduce the burden of extra visits include providing vaccination at all medical visits during the influenza season, and extending the vaccination season through February to increase coverage during the usual peak month of transmission, or who need second doses.…”
Section: Immunization Program Issuesmentioning
confidence: 99%
“…Among children aged 9 to 18 years, at least 75% would need 1 extra visit. 39 To be maximally effective and avoid missed opportunities to prevent early season infections, vaccination should occur as early as possible, beginning as early as September. Strategies to reduce the burden of extra visits include providing vaccination at all medical visits during the influenza season, and extending the vaccination season through February to increase coverage during the usual peak month of transmission, or who need second doses.…”
Section: Immunization Program Issuesmentioning
confidence: 99%
“…6,7,10 Because adolescents present infrequently for primary health care visits, 5,12 reminder/recall for adolescent immunizations is attractive in concept. 13,14 Nevertheless, little evidence exists for the effectiveness of practice-based reminder/recall for adolescent immunizations, 15,16 although in one recent study in 4 practices researchers demonstrated increased immunization rates. 17 Moreover, few practices actually use reminder/recall for patients of any age [18][19][20] ; barriers include the added workload, costs, and complexities of conducting such a program.…”
Section: Introductionmentioning
confidence: 99%
“…This increase will be a burden on primary care practices, given the time and resources needed to vaccinate the majority of adolescents. 3 Even though rates of influenza vaccinations are still low among adolescents, if they were to increase per current recommendations, the burden to primary health care providers could be significant. To address the need of patients to schedule travel to providers' offices, and the concerns of offices having to create resources to supply a potentially overwhelming demand, alternative immunization sites will be needed to deliver influenza vaccines to adolescents each year.…”
Section: Introductionmentioning
confidence: 99%